Resource Constructs Simulation in Sociology: Methodology, Theory, Practice - Yu. D. Krasovsky (Управление)
The main stages of origin, operation and development of simulation modeling process in sociology based on consulting activity, as well as simulation models construction methods in the business games’ specifics are outlined in this paper. The author reveals underexplored problems in sociology at the concrete descriptions of social technologies for match practice, “decoding” the simulation modeling phenomenon as a consultmanagement resources. An innovation in this phenomenon understanding is a discovery by the author of two new functions during its study: structural and training ones. In the sociological encyclopedic dictionary, where the simulation modeling phenomenon is described, only five of its functions has been stated.